2004
DOI: 10.1042/bj20031949
|View full text |Cite
|
Sign up to set email alerts
|

Acyl-CoA-binding protein, Acb1p, is required for normal vacuole function and ceramide synthesis in Saccharomyces cerevisiae

Abstract: In the present study, we show that depletion of acyl-CoA-binding protein, Acb1p, in yeast affects ceramide levels, protein trafficking, vacuole fusion and structure. Vacuoles in Acb1p-depleted cells are multi-lobed, contain significantly less of the SNAREs (soluble N -ethylmaleimide-sensitive fusion protein attachment protein receptors) Nyv1p, Vam3p and Vti1p, and are unable to fuse in vitro. Mass spectrometric analysis revealed a dramatic reduction in the content of ceramides in whole-cell lipids and in vacuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 52 publications
(70 reference statements)
5
73
1
Order By: Relevance
“…A human ortholog encodes a 2-hydroxylase that can work on free fatty acids, probably of various chain lengths, whereas the yeast enzyme appears to work on fatty acids only once they are attached to ceramide [36]. The essential fatty acyl CoA binding protein, Acb1p, is also required for efficient ceramide synthesis in yeast [37], and the mammalian Acb1p homolog is essential for the viability of mammalian tissue-culture cells [38]. Acb1p is most likely essential for efficient delivery or presentation of very long-chain fatty acids to the ceramide synthase in yeast.…”
Section: Dihydroceramide Synthase (Dhcers) (Reaction Vi)mentioning
confidence: 99%
“…A human ortholog encodes a 2-hydroxylase that can work on free fatty acids, probably of various chain lengths, whereas the yeast enzyme appears to work on fatty acids only once they are attached to ceramide [36]. The essential fatty acyl CoA binding protein, Acb1p, is also required for efficient ceramide synthesis in yeast [37], and the mammalian Acb1p homolog is essential for the viability of mammalian tissue-culture cells [38]. Acb1p is most likely essential for efficient delivery or presentation of very long-chain fatty acids to the ceramide synthase in yeast.…”
Section: Dihydroceramide Synthase (Dhcers) (Reaction Vi)mentioning
confidence: 99%
“…This phenotype is actually quite reminiscent of the depletion of the acyl CoA binding protein (Acb1), which does not seem to be directly connected to the fusion reaction. 166 Generally, it appears that vacuole dynamics are linked to the metabolic state of the cell and potentially connected to autophagy. 17 How sensing of nutrients occurs at the vacuole is not yet known.…”
Section: The Vacuole Fusion Machinerymentioning
confidence: 99%
“…Targeted disruption of the yeast ACBP gene (ACB1) revealed that ACBP deficiency results in increased levels of C18:0 acyl-CoA esters and a decrease in the amount of total C26:0 fatty acids, indicating that transport of FA toward elongation is impaired by lack of ACBP. Furthermore, sphingolipid and ceramide amounts were reduced, membrane structure was altered, and vesicular transport was compromised (23)(24)(25).…”
mentioning
confidence: 99%